Hydrothermal Synthesis and Crystal Structure of (4,4’-H2bipy)(ZnI4) - Wen-Tong, Chen; Cheng, Jiang (Asian Journal of Chemistry, 2011)
(4,4'-H2bipy)(ZnI4) (1) has been synthesized via hydrothermal reaction and characterized by single crystal X-ray diffraction. The crystal belongs to monoclinic, space group P21/c with a = 7.7756(6), b = 21.536(2), c = 10.9188(8) Å, β = 106.606(1)º, C10H10N2I4Zn, Mr = 731.17, V = 1752.1(2) Å3, Z = 4, Dc = 2.772 g/cm3, S = 1.002, μ(MoKα) = 8.433 mm-1, F(000) = 1304, R = 0.0239 and wR = 0.0544. The crystal structure analysis of (4,4'-H2bipy)(ZnI4) shows that this compound features an isolated structure, based on discrete 4,4'-H2bipy moieties and tetrahedral zinc atoms terminally coordinated by four iodine atoms. The 4,4'-H2bipy and ZnI4 moieties are interconnected by hydrogen bonds to yield a 1-D supramolecular chain.